Mechanism of luteolin against non-small-cell lung cancer: a study based on network pharmacology, molecular docking, molecular dynamics simulation, and in vitro experiments - Zhang, Jihang; Li, Changling; Li, Wenyi; Shi, Zhenpeng; Liu, Zhenguo; Zhou, Junyu; Tang, Jing; Ren, Zixuan; Qiao, Yun; Liu, Deshan (Frontiers in Oncology, 2024)
IntroductionLuteolin, a naturally occurring flavonoid compound, demonstrates promising anti-cancer properties. However, its mechanism against non-small-cell lung cancer (NSCLC) remains unknown. This study employed network pharmacology, molecular docking, molecular dynamics simulation (MDS), and in vitro experiments to investigate the potential mechanisms by which luteolin against NSCLC.MethodsInitially, the potential targets of luteolin and NSCLC-related targets were identified from public databases such as TCMSP, GeneCards, OMIM, DrugBank, and TTD. Subsequently, the protein-protein interaction (PPI) network screening and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted. The binding affinity and stability of luteolin with the core targets were assessed using molecular docking and MDS. Finally, the results were validated by in vitro experiments.ResultsA total of 56 luteolin targets and 2145 NSCLC-related targets were identified. Six core targets, TP53, EGFR, AKT1, TNF, JUN, and CASP3, were screened via the PPI network. The GO and KEGG analyses indicated that luteolin’s activity against NSCLC potentially involves PI3K-Akt, NF-kappa B, and other signaling pathways. Molecular docking revealed that luteolin had high binding affinity with the core targets. MDS confirmed the stable interaction between luteolin and key proteins TP53 and AKT1. in vitro, luteolin significantly inhibited the proliferation and migration of A549 cells, while also inducing apoptosis. In addition, luteolin downregulated the expression of p-Akt (Ser473), MDM2, and Bcl-2 but upregulated the expression of p53 and Bax, which was consistent with the effect of LY294002.ConclusionLuteolin had a good anti-NSCLC effect, and the apoptosis-inducing effect might be related to the Akt/MDM2/p53 signaling pathway.